Improvement of electric field mill signal conditioning unit and motor controller [electronic resource] - Nik Nurazam Wan Kamarudin, 1988-, author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2013